Návrh a tvorba informačního systému pro optiky - Komínek, Vít (Vysoké učení technické v Brně. Fakulta podnikatelská, 2020)
Diplomová práce je zaměřena na analýzu, návrh a tvorbu vlastního informačního systému vytvořeného pro oční optiky. Informační systém bude provázet uživatele v převážné většině procesů spojených s provozem pobočky oční optiky.

This master’s thesis is focused on the analysis, design and creation of an information system created for ophthalmic opticians. This information system will accompany users in the vast majority of processes associated with the operation of the optician's branch.
Design and Creation of Information System for Opticians
Keywords: návrh; informační systém; optik; SQL; databáze; proces; Delphi; analýza; design; information system; optician; SQL; database; process; Delphi; analysis